Hypnosis As An Replacement Of Anesthesia In Surgery (Literature Review) - Eko Mulyadi; Evy Aristawati (International Journal of Health Engineering and Technology, 2023)
Hypnosis has been used to deal with acute and chronic pain, anxiety, and other positive benefits before, during and after surgery. But in the field, hypnosis was still a little used even there were still many who doubt its effectiveness.We conducted an article review in English using keywords: hypnosis, anesthesia, surgery, with a time span since 1846 until 2019, with 20 articles selected on Google Scholar, PubMed, Science Direct, and The National Library of the Republic of Indonesia (PNRI) portal.Mesmerism hypnosis and ericsonian hypnosis have been used for anesthesia, since prior to the discovery of chemical anesthesia, the use of chemical anesthesia has made hypnosis no longer used as the main anesthetic in surgery, but in certain cases such as patients with multiple chemical sensitivity or patients with contra-indications of general anesthesia , hypnosis was still used as the main anesthetic in surgery, hypnosis was currently widely used in perioperative, the use of hypnosis with chemical anesthesia can increase its benefits, and there were no reports of side effects. Hypnosis can be used as a major anesthetic, further research with a good design such as a randomized control trial about the use of hypnosis as anesthesia.